The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1128/.74.10.4448-4455.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Human Immunodeficiency Virus Type 1 gp120 V2 Domain Mediates gp41-Independent Intersubunit Contacts

Abstract: The envelope protein of human immunodeficiency virus type 1 HIV-1 undergoes proteolytic cleavage in the Golgi complex to produce subunits designated gp120 and gp41, which remain noncovalently associated. While gp41 has a well-characterized oligomeric structure, the maintenance of gp41-independent gp120 intersubunit contacts remains a contentious issue. Using recombinant vaccinia virus to achieve high-level expression of gp120 in mammalian cells combined with gel filtration analysis, we were able to isolate a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Given that viruses lacking the V1/V2 region or the V2 variable loop are capable of replication 74,75 , this region cannot be essential for infectivity and therefore is relatively unconstrained in terms of mutation. Therefore, despite the fact that this region of the virus envelope carries out important functions -mediating gp41-independent interaction within the gp120 trimer 76 and shielding the region in and around the bridging sheet of gp120 responsible for interaction with chemokine receptors 74,75,77-79 -the V1/V2 loop is an improbable target for vaccines and, in fact, is specifically being deleted in some vaccine constructs to provide better access to neutralizing epitopes in and near the co-receptor binding site 80 .…”
Section: Variable Regions Of the Virus Envelope As Targetsmentioning
confidence: 99%
“…Given that viruses lacking the V1/V2 region or the V2 variable loop are capable of replication 74,75 , this region cannot be essential for infectivity and therefore is relatively unconstrained in terms of mutation. Therefore, despite the fact that this region of the virus envelope carries out important functions -mediating gp41-independent interaction within the gp120 trimer 76 and shielding the region in and around the bridging sheet of gp120 responsible for interaction with chemokine receptors 74,75,77-79 -the V1/V2 loop is an improbable target for vaccines and, in fact, is specifically being deleted in some vaccine constructs to provide better access to neutralizing epitopes in and near the co-receptor binding site 80 .…”
Section: Variable Regions Of the Virus Envelope As Targetsmentioning
confidence: 99%
“…Methods for the estimation of average partial specific volumes have been described by Shire (1992), Junghans et al (1996), Fairman et al (1999), and Lewis and Junghans (2000). For glycosylated proteins, the availability of molar mass data from mass spectrometry is extremely helpful, because, together with the molar mass of the protein component as calculated from amino acid composition, the molar mass of the carbohydrate component can be estimated (Fairman et al, 1999;Center et al, 2000). A technique in which two SE experiments are performed simultaneously, one in D 2 O and one in H 2 O (Edelstein and Schachman, 1967), can be useful in the study of glycosylated proteins.…”
Section: Size Partial-specific Volume and Prior Characterization Ofmentioning
confidence: 99%
“…Major findings of this work are that (i) the SU subunit of the SARS-CoV S glycoprotein (S1) forms dimers, (ii) the dimerization domain does not overlap and is upstream of the RBD, (iii) its deletion abolishes fusion, (iv) dimeric S1 binds receptor molecules much more efficiently than monovalent fragments containing the RBD, and (v) the soluble S ectodomain forms trimers under gel filtration conditions. It has been previously reported that some attachment SU subunits of class I fusion proteins that bind receptor molecules can form dimers including gp120 of the retrovirus HIV-1 [17] and S1 of the coronavirus MHV [16]. What is the role of S1 dimerization for mediation of membrane fusion however remains unclear.…”
Section: Discussionmentioning
confidence: 99%